Valorization of cricket, Acheta domesticus (Linnaeus, 1758), flour as a source of dietary protein in Japanese quail, Coturnix japonica (Temminck and Schlegel, 1849), farming - Kouatcho, Francois Djitie; Rusu, Razvan Mihail Radu; Mohamadou, Bachirou; Aoudou, Bobga; Pop, Ioan Mircea; Usturoi, Marius Giorgi; Tinkeu, Léonard S Ngamo (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Quail production is ranked as an important alternative animal protein source in Cameroon. One of the main constraints of this production is the quality of feed, which lacks protein that is regularly supplied by fish meal. To avoid disagreements due to the constant shortage of fish meal, alternative protein sources are needed, and among them are crickets(Acheta domesticus). The goal of this study was to find out how well Japanese quails could be raised if fish meal was replaced with cricket meal. Materials and Methods: A total of 192, 4-week-old quails were divided into 12 similar sets of 8 females and 8 males. The Four experimental diets (T00, T15, T30, and T45) were all formulated based on the level (0%, 15%, 30%, and 45%, respectively) of fish meal substitution with cricket meal in the basal diet (crude protein: 20.18% and ME: 3,013.78 kcal/kg) and randomly assigned to three sets in a completely randomized design consisting of four treatments each repeated three times. Growth, carcass, and some reproduction parameters were collected. The data were analyzed using one-way analysis of variance and the Duncan test, with a significance level of 5%. Results: Cricket meal diets increased body weight in males (204.32 ± 5.69 gm for T45) and regardless of the sex (226.72 ± 29.45 gm for T30) compared to 184.17 ± 3.11 gm and 214.55 ± 32.77 gm for the control group, respectively. In females, substitution at 30% increased body weight (253.80 ± 6.48 gm), while 45% induced a reduction (216.67 ± 6.49 gm) when compared to the control group value (244.92 ± 6.07 gm). Carcass yield and the proportion of different parts were not significantly affected by the experimental diets. Liver proportions were significantly higher at 15% and 35% cricket meal incorporation compared to 45%. First songs and egg laying were recorded at 7 weeks with T15, which also led to improved egg laying performance compared to the other treatments. Ovaries were poorly developed in the T45 females compared to the other treatments. Conclusions: Cricket flour might be a good candidate as a locally available protein source to substitute fish meal in the Japanese quail’s diet at the finisher and reproductive stages, and the level of 30% seems to be more efficient. J. Adv. Vet. Anim. Res., 9(2): 310–322, June 2022 http://doi.org/10.5455/javar.2022.i598